1983
DOI: 10.1093/oxfordjournals.eurheartj.a061384
|View full text |Cite
|
Sign up to set email alerts
|

Different hemodynamic actions of trinitroglycerin and isosorbide dinitrate in patients with acute myocardial infarction

Abstract: The hemodynamic effects of intravenously administered trinitroglycerin (TNT) and isosorbide dinitrate (ISDN) in stechiometric equivalent doses were studied in 30 patients with acute myocardial infarction. Both drugs were given over 30 min in every patient, and the stability of the condition of the patient was checked by administering the initial drug again. Measurements were made by right heart catheterization using a balloon tip thermodilution catheter and a catheter in the radial artery. TNT and ISDN have di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
3
3
0
Order By: Relevance
“…In conclusion, ISDN may be classified as a mixed agent acting on both preload and afterload, which is in agreement with earlier published results in patients (Rezakovic et al 1983).…”
Section: Discussionsupporting
confidence: 92%
“…In conclusion, ISDN may be classified as a mixed agent acting on both preload and afterload, which is in agreement with earlier published results in patients (Rezakovic et al 1983).…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study confirmed our previous findings that NTG action is pre dominant on the preload and in second place on the afterload level [18], and clearly showed that optimal indication for NTG ad ministration are the patients in subsets I and II, i.e. those with normal or elevated pulmo nary wedge pressure and normal mean ar terial pressure and Cl.…”
Section: Discussionsupporting
confidence: 90%
“…These results suggest that ISDN has a more selective action on venous vasculature than TNG. However, Rezakovic and colleagues [5], who compared TNG and ISDN in stoichiometrically equivalent doses by infusing them in a dose ratio 1:1.5 over 30 min in patients with acute myocardial infarction, found that TNG influenced predominantly pulmonary artery pressure and cardiac filling pressures, while ISDN affected cardiac output and systemic vascular resistance. They concluded that TNG is predominantly a venous dilator, while ISDN is a mixed vasodilator.…”
Section: Discussionmentioning
confidence: 99%
“…Thus nitrates decrease cardiac filling pressures relatively more than systemic vascular resistance, arterial blood pressure and cardiac output. However, there are in vitro [3,4] and in vivo [5] studies showing that various organic nitrates have different potency and selectivity in their effects on the venous and arterial beds, although the results are in part conflicting. In some situations, for example in the presence of increased myocardial oxygen consumption in association with systemic hypotension as a consequence of ischaemia-induced left ventricular failure and dilatation of the heart, it may be beneficial to give a nitrate which is more selective in its effect on the venous than on the arterial vascular bed.…”
mentioning
confidence: 99%